Immunological Complications and Treatment of Cryptorchidism in Children: A Surgical and Immunotherapeutic Perspective - Azis Elgondiev; Mustofa Aidid; Talant Omurbekov; Bolotbek Esembaev; Vladimir Poroshchai; Bakit Duysheubaev Oruzbaev; Chyngyz Temirkulov; Safiyat Emiraslanova; Yethindra Vityala (Trends in Immunotherapy, 2025)
Cryptorchidism, a common congenital urogenital abnormality affecting 1–5% of full-term male infants, involves the failure of the testicles to descend into the scrotum. This study aimed to evaluate the surgical outcomes in children with cryptorchidism and the effectiveness of rituximab-based immunotherapy for associated paraneoplastic autoimmune encephalitis. This study assessed the surgical outcomes of 1,290 children aged 8 months to 15 years who were treated for cryptorchidism at two facilities in Bishkek, Kyrgyzstan, between 2021-2024. Patients underwent surgery based on testicular location, with 134 treated using the Torek method, 1,055 using the Sokolov method, and 101 using the Petrivalsky/Shoemaker methods. Of the patients who underwent surgery before the age of 3 years, 46.4% had better outcomes. The inguinal region was the most common testicular location (97.1%), with 2.9% of the cases involving abdominal testes. Postoperative ultrasound revealed complications in 62.9% of patients who underwent the Torek method. Three patients with anti-N-methyl-D-aspartate receptor encephalitis associated with germ cell tumors were treated with tumor resection, corticosteroids, plasmapheresis, and rituximab, resulting in neurological recovery in all cases. This study emphasizes the importance of early surgical intervention and multidisciplinary management of cryptorchidism and its associated complications.